2020
DOI: 10.30597/mkmi.v16i4.9826
|View full text |Cite
|
Sign up to set email alerts
|

Disability and Depression among Population Aged 18-59 Years in Central Sulawesi Province: Analysis of Riskesdas 2018

Abstract: The prevalence of depression among the general population in CentralSulawesi was the highest in Indonesia (12.3%). Scholars revealed thatdisability was one of the main contributing factors of depression and in Central Sulawesi almost half of population was reported having disability (42.1%). This study was intended to identify the association of disability and depression in Central Sulawesi. Cross sectional design study was conducted with utilization of secondary data collection from Riskesdas 2018. Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, the prevalence of probable depression had not reached the pre-pandemic level. Basic health research in 2018 found that the national prevalence of depression was 6.1% [27]. This information was noteworthy as an alarming message.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence of probable depression had not reached the pre-pandemic level. Basic health research in 2018 found that the national prevalence of depression was 6.1% [27]. This information was noteworthy as an alarming message.…”
Section: Discussionmentioning
confidence: 99%